OPTIMALISASI PERMAINAN MONOPOLI SEBAGAI ALAT PENGEMBANGAN PSIKOSOSIAL DAN KEPERCAYAAN DIRI SISWA SD - Muthoharoh, Maratul; Rejeki, Asri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this study is to evaluate the effectiveness of the Monopoly game as an intervention to enhance self-confidence in fourth-grade students at SD NU Nurul Ishlah. This research employs a pre-experimental design with a "one group pre-test-post-test" model, allowing a comparison of students"™ self-confidence levels before and after the intervention within the same group. Four students identified with low self-confidence were selected based on initial assessments, and data were gathered through self-confidence questionnaires and observational sheets during three sessions of guided Monopoly gameplay. The findings reveal a significant increase in selfconfidence, evidenced by a marked improvement in post-test scores compared to pre-test scores, with a calculated effect size of 4, indicating a high impact of the intervention. The Monopoly game thus fostered a dynamic learning environment, encouraging active engagement, communication, and strategic thinking, all of which contributed to boosting the students"™ self-assurance. This study underscores the importance of incorporating interactive and engaging teaching methods, such as educational games, to support both the academic and psychological growth of primary school students, demonstrating that such interventions can play a valuable role in fostering a positive classroom atmosphere and enhancing students' personal development.